Comprehensive analysis of transcriptomics and metabolomics provides insights into the mechanism by plant growth regulators affect the quality of jujube (Ziziphus jujuba Mill.) fruit. - Defen Liu; Na Jiang; Yuting Yuan; Hejiang Liu; Yanjun Ju; Wanjin Sun; Wenzhao Jia; Yi Fang; Duoyong Zhao; Jiefei Mao; Lu Kang (PLoS ONE, 2024)
A comprehensively analysis of the transcriptomics and metabolomics was conducted to investigate the mechanism of plant growth regulators on the quality of jujube fruit. After the application of plant growth regulators, a total of 3097 differentially expressed genes (DEGs) were identified, which were mainly annotated in 123 pathways such as flavonoid biosynthesis, metabolism of alanine, aspartate, and glutamate. In addition, 1091 differential expressed metabolites (DEMs), including 519 up-regulated and 572 down-regulated metabolites, were significantly altered after application of plant growth regulators. DEGs and DEMs simultaneously annotated 69 metabolic pathways, including biosynthesis of phenylpropane, flavonoid, starch and sucrose. The key genes in flavonoid biosynthesis pathway were revealed, which may play an important role in plant growth regulator regulation quality of jujube fruit. Besides, the application of plant growth regulator during the jujube flowering period increased the contents of gibberellin and indole-3-acetic acid in leaves, and decreased the contents of abscisic acid. The results may help to reveal the metabolic network and molecular mechanism of plant growth regulators in jujube fruit.